Konsep Mutu, Mutu Sekolah, Mutu Lembaga Pendidikan Sekolah - Makmur Syukri; Muhammad Ridho Alfattah (Journal on Education, 2024)
Quality is the main need of every person, every institution and even every country, so the slogan Quality is everybody's business emerged, where efforts to obtain and improve quality are everyone's main agenda. Quality is a challenge for business and educational institutions because they are faced with the problem of how to manage quality in the face of global competition. A school that is "quality" oriented is required to always move dynamically, full of innovation efforts, and condition itself as a learning institution or organization that always pays attention to the demands of society's continuously developing needs. For this reason, schools are required to always try to perfect the design or standards of educational processes and outcomes so that they can produce "graduates" who meet the demands of society.